Corpses, coffins, and crypts : a history of burial - Colman, Penny (New York : Henry Holt, 1997)
Documents the burial process throughout the centuries and in different cultures.
Includes bibliographical references (p. 196-201) and index.
Keywords: Funeral rites and ceremonies -- History -- Juvenile literature; Burial -- Juvenile literature; Death -- Social aspects -- Juvenile literature; Funeral rites and ceremonies -- History; Burial -- History